2020
DOI: 10.3390/agriculture10050189
|View full text |Cite
|
Sign up to set email alerts
|

Autonomous Mowing and Turf-Type Bermudagrass as Innovations for An Environment-Friendly Floor Management of a Vineyard in Coastal Tuscany

Abstract: The establishment of permanent cover crops is becoming a common practice in vineyard floor management. Turfgrass science may provide species and techniques with a high potential for improving the sustainability of vineyard floor management. Based on this assumption, an experiment was carried out during 2018 and 2019 at the Donna Olimpia Vineyard, Bolgheri, Italy. The trial aimed at comparing an innovative floor management system based on a turf-type cultivar of bermudagrass mown with an autonomous mower with a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
13
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5

Relationship

4
1

Authors

Journals

citations
Cited by 11 publications
(15 citation statements)
references
References 26 publications
2
13
0
Order By: Relevance
“…A smaller distance between the cutting disc and the cowling may prevent weeds from growing tall close to the vines trunks and improve the overall working efficiency of the autonomous mower in terms of weed control. The results regarding the primary energy consumption estimation highlight that the AM system provides for a more sustainable vineyard floor management, corroborating findings reported by Magni et al [28]. Moreover, vineyard floor management does not require daily mowing; thus, a single autonomous mower can be employed to manage different sectors of a vineyard, further improving autonomous mowers working efficiency and overall energy savings [10].…”
Section: Management Systemsupporting
confidence: 85%
See 4 more Smart Citations
“…A smaller distance between the cutting disc and the cowling may prevent weeds from growing tall close to the vines trunks and improve the overall working efficiency of the autonomous mower in terms of weed control. The results regarding the primary energy consumption estimation highlight that the AM system provides for a more sustainable vineyard floor management, corroborating findings reported by Magni et al [28]. Moreover, vineyard floor management does not require daily mowing; thus, a single autonomous mower can be employed to manage different sectors of a vineyard, further improving autonomous mowers working efficiency and overall energy savings [10].…”
Section: Management Systemsupporting
confidence: 85%
“…Results from its application highlighted that autonomous intra-row weed management is a safe and reliable technique that helps to save energy. Magni et al [28] obtained similar results by testing an autonomous mower to manage a perennial grass complete cover vineyard floor. In this trial, significant reductions of power consumption and CO 2 emissions were observed compared to the ordinary technique.…”
Section: Introductionmentioning
confidence: 74%
See 3 more Smart Citations